FORMATION OF INTER-CULTURAL COMPETENCE OF FUTURE LAWYERS AT BASIC TRAINING IN HIGHER EDUCATIONAL INSTITUTIONS - Korotkova, Yuliya (Educological discourse, 2019)
The article reveals the essence of the concept of "intercultural competence of the future lawyer", which is to be interpreted as an integrative, multileveled, professional personal quality that synthesizes a set of knowledge, skills, attitudes, values, determined by the goals and objectives of intercultural communication on the basis of mutual respect, mutual understanding and mutual enrichment. Intercultural competence is considered as an integral system which consists of certain components, relatively independent, but interrelated and interdependent. These include: communicative, socio-cultural, motivational-value, affective, cognitive ones. It is proved that the formation of intercultural competences of lawyers will promote the application of innovative methods and forms of training (business/role games, debates, discussions, disputes, modellings, simulations, etc.), among which intercultural training is of particular importance. The latter aims at familiarizing its participants with intercultural differences, role-playing the specially created situations of intercultural communication that help students in better understanding of the existing cultural differences, and to teach them to build their relationships with representatives of other cultural environments on the basis of tolerance. In this regard, it will be efficient to organize and conduct such trainings as: "Convention on the Protection of Human Rights and Fundamental Freedoms", "Communication in the work of a lawyer"; "Working with vulnerable groups of clients of the system of free legal aid"; "My professional development"; "International humanitarian law", "All are equal – all are united", etc. Also important are intercultural workshops aimed at cultivating tolerance, for example, "Tolerance. Prevention of xenophobia", "Intercultural communication and ethnic stereotypes", etc.